2015
DOI: 10.1177/1528083714567240
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high temperature on the performance of filter fabric

Abstract: High-temperature filtration is one of the most promising developments in particle collection technology. Process gases if cleaned (filtered) at elevated temperatures, then processes can be made more efficient in terms of energy and more integrated in terms of process technology. The present study embodies the effect of high temperature and dust concentration on the performance of different filter media (P84 with PTFE scrim and P84 with P84 scrim) in terms of emissions, filtration efficiency, pressure drop and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…Polytetrafluoroethylene (PTFE), para-aramid (PA), polyester fibers (PET), polyphenylene sulfide (PPS) and polyimide (P84) [28][29][30][31][32] are commonly used nonwoven materials for particulate matter filtration. Among them, the PPS nonwoven has been widely applied to waste gas filtration, especially in some industrial waste gases with high humidity due to its excellent properties such as high temperature resistance, chemical corrosion resistance and hydrolysis resistance [33].…”
Section: Introductionmentioning
confidence: 99%
“…Polytetrafluoroethylene (PTFE), para-aramid (PA), polyester fibers (PET), polyphenylene sulfide (PPS) and polyimide (P84) [28][29][30][31][32] are commonly used nonwoven materials for particulate matter filtration. Among them, the PPS nonwoven has been widely applied to waste gas filtration, especially in some industrial waste gases with high humidity due to its excellent properties such as high temperature resistance, chemical corrosion resistance and hydrolysis resistance [33].…”
Section: Introductionmentioning
confidence: 99%
“…PPS nonwoven fabric filter material is a cost-effective filter material used in processing the flue gas of coal-fired power plants. ,,,− In China, approximately 80% of the PPS filter material is used in coal-fired boilers . The service life of a PPS filter bag can reach 5 years provided that the bag is maintained and used properly.…”
Section: Introductionmentioning
confidence: 99%
“…The service life of a PPS filter bag can reach 5 years provided that the bag is maintained and used properly. However, the service lives of some PPS filter materials of electrostatic–bag composite precipitators have been substantially shortened. , Research has suggested that the O 3 produced via corona discharge is the primary reason for the shortened service life of filter materials, whereas other researchers could not detect O 3 in the electrostatic–bag precipitator using on-site tests, thus making the problem difficult to solve.…”
Section: Introductionmentioning
confidence: 99%
“…The major factors contributing to the degradation of PPS filter bags can be attributed to the oxidation and acid-based corrosion. 3,7–10…”
mentioning
confidence: 99%
“…The major factors contributing to the degradation of PPS filter bags can be attributed to the oxidation and acidbased corrosion. 3,[7][8][9][10] Flue gas discharged from refuse incineration plants, steel plants, cement plants, and thermal power plants often contains some oxidative gases, such as NO x , SO x , and Cl 2 . The PPS macromolecular chain is composed of phenyls rings linked with sulfur atoms alternately.…”
mentioning
confidence: 99%